Kesiapsiagaan dan Pembentukan Kelurahan Tangguh Sebagai Langkah Meminimalisir Resiko Bencana - Aldino, Pravinska; Pristiana, Alvira Febrian; Rosida, Siti Maulani (Lembaga Penerbitan Universitas Esa Unggul, 2023)
Disaster is one thing that humans cannot predict, even when disasters that come often have very detrimental effects, such as loss of life and material to damage to facilities and infrastructure. So we need a solution to find out what handling is done to anticipate the coming of a disaster and how to reduce the risk of a disaster. The research design used is the literature review method, namely research conducted by researchers through a variety of literary information (the relevant textbooks or handbooks or scientific journals). The focus of literature research is to find various theories, laws, propositions, principles, or ideas that are used to analyze and solve the formulated research questions. Forum Pengurangan Resiko Bencana (FPRB) as an effort to increase awareness and preparedness in anticipating the arrival of disasters will make the community respond quickly and appropriately so that the process of recovery, maintenance and handling can be carried out immediately. Efforts to establish a Forum Pengurangan Resiko Bencana (FPRB) are part of the strategy to create resilient urban villages because it includes activities to increase awareness and preparedness in anticipating future disasters. With the Forum Pengurangan Resiko Bencana (FPRB) the government and the community are on standby and working together to respond in the event of a disaster. If so far, when a disaster occurs, the community is completely dependent on the government, it is hoped that by involving the community, independence will emerge to actively participate in dealing with disasters both during the pre-disaster, disaster and post-disaster formation. as well as encouraging cooperation with various sectors to encourage preparedness efforts in anticipating disasters. In carrying out village resilience activities, stakeholders together with the community should carry out an assessment of the disaster risks that exist in the area. The assessment consists of three components, namely threat assessment, vulnerability assessment and capability assessment. Forum Pengurangan Resiko Bencana (FPRB) the community is provided socialization and training on disaster which aims to create an awareness of the community so that they have knowledge and skills in overcoming disaster problems that may arise in the future.